2015
DOI: 10.1177/1541344615602758
|View full text |Cite
|
Sign up to set email alerts
|

Paving Paths Toward Transformation With Incarcerated Women

Abstract: The purpose of this study was to elicit the experiences of women who participated in a gender-responsive program in jail. Through the collection of life history interviews, this article highlights the transformative learning experiences of 13 women participants. Research questions included (1) how did the program foster transformative learning? (2) What effect did the program have on participants' thinking, feeling, and behavior? Despite the highly regimented and regulated jail context-an environment where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…At this stage the respondents began to alter the meaning scheme of drug addiction. Individuals successfully reflect on their past experiences as drug addicts and experience a positive perspective in transforming the new life and it is support the findings by Sandoval, Baumgartner dan Clark [28] dan Varas [29]. In Islam the reflection is also known as the Muhasabah which individuals reflect on the mistakes they have done before.…”
Section: Discussionsupporting
confidence: 72%
“…At this stage the respondents began to alter the meaning scheme of drug addiction. Individuals successfully reflect on their past experiences as drug addicts and experience a positive perspective in transforming the new life and it is support the findings by Sandoval, Baumgartner dan Clark [28] dan Varas [29]. In Islam the reflection is also known as the Muhasabah which individuals reflect on the mistakes they have done before.…”
Section: Discussionsupporting
confidence: 72%
“…The staff focus group findings were consistent with studies concluding noncognitive strategies including dialogue, storytelling, social interaction, and space for engagement (Merriam & Bierema, 2014) fostered TL. They confirmed the significance of safe environments and opportunities for dialogue as conducive to acceptance and enhanced self-esteem for marginalized women in troubling contexts (Alderson & Twist, 2003; Sandoval et al, 2016). The Shelter’s “intangible” program goals confirmed Rivera’s (2003) assessment as supporting an ideal TL context for advancing empowerment learning goals.…”
Section: Discussionmentioning
confidence: 69%
“…Some have been documented as supporting marginalized women’s TL in troubling contexts. For example, Sandoval et al (2016) found incarcerated women in a gender-responsive jail program experienced transformation through interpersonal and intrapersonal engagement. Similarly, Alderson and Twist (2003) examined the impact of literacy activities on the lives of women working as sex trade workers in Vancouver that sought to provide “…safety, acceptance, challenge and opportunities for increased self-esteem within the context of chaos, grinding poverty, violence and substance abuse” (p. 8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further studies demonstrate that participation in art therapy programs has a positive impact on confidence levels, listening and communication skills, distress tolerance, levels of self-expression, enhanced levels of engagement with further education and training, an improved ability to cope with stressors of prison life, and an overall positive behavioral change (Sandoval, Baumgartner, & Clark, 2015). Participants further described art as a safe way to express, release, and deal with potentially destructive feelings, as well as to form positive relationships with both their instructors and peers (Gussak, 2007).…”
Section: Art and Expressionmentioning
confidence: 99%